Measurements of the ablation-front trajectory and low-mode nonuniformity in direct-drive implosions using x-ray self-emission shadowgraphy. (2015) - Michel, D.T.; Davis, A.K.; Armstrong, W.; Bahr, R.; Epstein, R.; Goncharov, V.N.; Hohenberger, M.; Igumenshchev, I.V.; Jungquist, R.; Meyerhofer, D.D.; Radha, P.B.; Sangster, T.C.; et al.
Abstract : Self-emission x-ray shadowgraphy provides a method to measure the ablation-front trajectory and low-mode nonuniformity of a target imploded by directly illuminating a fusion capsule with laser beams. The technique uses time-resolved images of soft x-rays ( >1 keV) emitted from the coronal plasma of the target imaged onto an x-ray framing camera to determine the position of the ablation front. Methods used to accurately measure the ablation-front radius ( δR=± 1.15 μm ), image-to-image timing ( δ(Δt)=± 2.5 ps) and absolute timing ( δt=± 10 ps) are presented. Angular averaging of the images provides an average radius measurement of δ(R_av)=± 0.15 μm and an error in velocity of δV/V=± 3% . This technique was applied on the Omega Laser Facility [Boehly et al., Opt. Commun.133, 495 (1997)] and the National Ignition Facility [Campbell and Hogan, Plasma Phys. Control. Fusion41, B39 (1999)].